Theoretical methods for measuring chemo-physical properties of nucleic acids during the oxidation of DNA and the incidence of cancer - Imanzadeh, Mehdi; Zare, Karim; Monajjemi, Majid; Shamel, Ali (Revista de la Universidad del Zulia, 2020)
The purpose of this papers is to investigate theoretical methods to measure the chemo-physical properties of nucleic acids during DNA radicalization and cancer incidence. For this purpose, structures consisting of DNA nucleotides were considered and all structures were optimized using DFT at the CAM-B3LYP / 6-31G level and spatial parameters such as bond length, HOMO and LUMO orbitals, and thermodynamic parameters were obtained, as well as NMR spectroscopy. The results showed that the guanine base had better conditions for oxidation compared to other bases. Also in the NMR calculations using the GIAO method we were able to examine the single and double chain structure in different states when it is natural and abnormal. Therefore, in this work, we try to find a normal relationship between chemical displacement and the rate of natural state DNA aberration, by studying the comparison of isotropic and anisotropic parameters with respect to DNA bases such as adenine, guanine, cytosine, thymine. It was concluded that the skewness (η) is between (0.1) and the skewness is between (1-1), which can be correlated with the abnormalities of the DNA base from the normal to abnormal state. It was also found that the phosphate group oxygen atom in the abnormal form showed most of the changes in these parameters compared to the natural form.